Testing of seismic dampers with replaceable U-shaped steel plates. (15th January 2019) - Qu, Bing; Dai, Chunxue; Qiu, Jin; Hou, Hetao; Qiu, Canxing
Highlights: The damper has an excellent hysteretic energy dissipation capacity. The damper exhibits a stable post-visible-rupture behavior. The damper can be promptly repaired after a major earthquake. The repaired damper behaved as the original one. The model predicts acceptable results for yield and ultimate strengths of the damper. Abstract: This research focused on a new type of seismic damper consisting of replaceable U-shaped steel plates. To investigate behavior of the damper, seven specimens were tested. The test parameters varied in these specimens included geometries and materials of the U-shaped steel plates and the loading protocols. Test results show that the specimens exhibited stable hysteretic behaviors and satisfactory energy dissipating capacities. In addition, this research provided clear evidence that the damper is robust and tolerant to the ruptures in the U-shaped steel plates. Some specimens continued to dissipate significant amounts of hysteretic energy even after formation of the visible ruptures in the U-shaped steel plates. Moreover, this research demonstrated that the damper repaired through replacement of the U-shaped steel plates following a severe earthquake remained satisfactory in a subsequent earthquake. Further, this paper presents the equations for estimating yield strength and ultimate strength of the damper. It was found that the derived equations provide reasonable predictions and can be used for future design.